Experimental hyperthermia: expression of proteins involved in the regulation of ovarian corpus luteum apoptosis in the acute and recovery periods - S. V. Michurina; S. I. Kolesnikov; I. Yu. Ishchenko; S. A. Arkhipov (Acta Biomedica Scientifica, 2022)
Background.Heat shock effects can initiate apoptosis of oocytes and corpus luteum cells in mammalian ovaries. During folliculogenesis, follicular apoptosis is regulated by Bcl-2 and BAX proteins which are key effectors of granular cell death. Mechanisms of disruption of the ovarian corpus luteum development under heat stress remain largely unclear.Aim of the research: to identify the expression features of anti-apoptotic Bad and proapoptotic Bcl-2 proteins in the rat ovarian luteocytes in the acute (by day 3) and recovery (by days 7 and 14) periods after a single exposure of experimental hyperthermia (EH) (rectal temperature 43.5 °C).Materials and methods. The expression of Bad and Bcl-2 was determined immunohistochemically using an indirect two-stage streptavidin-biotin method.Results. On day 3 after EH, the expression areas of both Bad and Bcl-2 increased 2-fold, but the ratio of Bcl-2/Bad areas did not change, indicating that the intensity of apoptosis along the mitochondrial pathway in luteocytes in the acute period was  maintained within physiological values. On day  7, the Bad and Bcl-2 expression areas remained at the level of day 3, but the Bcl-2/Bad index decreased, indicating the activation of the apoptosis internal pathway in the ovarian corpus luteum cells. By day 14, the protein expression areas decreased (Bad – by 1.7 times, Bcl-2 – by 3.2 times) compared to the acute period, and the Bcl-2/Bad index decreased by 2 times compared to the control and the acute period group.Conclusion. The observed predominance of proapoptotic Bad protein over antiapoptotic Bcl-2 in luteocytes on day 14 after EH indicates the anti-apoptotic protection violation, which leads to the apoptosis mitochondrial pathway activation of  the latter. A decrease in Bcl-2 expression can be regarded as a manifestation of the defective luteocytes removal mechanism and the body’s desire to normalize the ovarian-uterine cycle disrupted by high temperature exposure.